Formative Assessment Practices in an Elementary EFL Classroom: Implementation and Challenges - Najwa Fatika; Maskhurin Fajarina (International Journal of Research in Education, 2026)
This study explored the implementation of formative assessment practices in an elementary English classroom at MI Perguruan Mu’allimat. The study aimed to identify how formative assessment was implemented during the teaching and learning process and to examine the challenges faced by the teacher during its implementation. This study employed a qualitative descriptive design involving one English teacher and classroom interaction in Grade 5C as the focus of the study. The data were collected through classroom observation, interviews, and documentation, and were analyzed using the interactive model proposed by Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings revealed that formative assessment was implemented through oral questioning, prompting and corrective feedback, and classroom monitoring during classroom activities. These practices were used not only to identify students’ understanding but also to encourage participation and maintain classroom interaction during the lesson. The study also identified several challenges in implementing formative assessment, including students’ passive participation, differences in students’ understanding, and limited classroom continuity caused by school activities and schedule interruptions. The findings indicate that formative assessment practices in elementary English classrooms are strongly influenced by classroom context and students’ participation patterns. Therefore, teachers need to apply flexible formative assessment strategies that support both students’ learning and classroom engagement.